Challenges to the census: international trends and a need to consider public health benefits. (October 2017) - Wilson, R.T.; Hasanali, S.H.; Sheikh, M.; Cramer, S.; Weinberg, G.; Firth, A.; Weiss, S.H.; Soskolne, C.L.
Abstract: The Canadian government decision to cancel the mandatory long-form census in 2010 (subsequently restored in 2015), along with similar discussions in the United Kingdom (UK) and the United States of America (USA), have brought the purpose and use of census data into focus for epidemiologists and public health professionals. Policy decision-makers should be well-versed in the public health importance of accurate and reliable census data for emergency preparedness planning, controlling disease outbreaks, and for addressing health concerns among vulnerable populations including the elderly, low-income, racial/ethnic minorities, and special residential groups (e.g., nursing homes). Valid census information is critical to ensure that policy makers and public health practitioners have the evidence needed to: (1) establish incidence rates, mortality rates, and prevalence for the full characterization of emerging health issues; (2) address disparities in health care, prevention strategies and health outcomes among vulnerable populations; and (3) plan and effectively respond in times of disaster and emergency. At a time when budget and sample size cuts have been implemented in the UK, a voluntary census is being debated in the US. In Canada, elimination of the mandatory long-form census in 2011 resulted in unreliable population enumeration, as well as a substantial waste of money and resources for taxpayers, businesses and communities. The purpose of this article is to provide a brief overview of recent international trends and to review the foundational role of the census in public health management and planning using historical and current examples of environmental contamination, cancer clusters and emerging infections. Citing a general absence of public health applications of the census in cost-benefit analyses, we call on policy makers to consider its application to emergency preparedness, outbreak response, and chronic disease prevention efforts. At the same time, we call on public health professionals to improve published estimates of monetary benefit (via either cost-benefit or cost-effectiveness analysis) to a given public health intervention. Highlights: Recent governmental actions in Europe and North America threaten the availability of reliable census information. Census information is critical for effective health improvement and emergency preparedness planning. Threats to the census are threats to evidence-based decision-making.